The whole truth - Garaudy, Roger; Ross, Peter; Ross, Betty (London : Fontana, 1971)
This text repudiates the accusations made against the auhor by the French Communist Party - from which he was subsequently expelled.
Translation of Toute la vérité.
Keywords: Parti communiste français; Communism; Κομμουνισμός.